Comparison of traditional and next-generation oral anticoagulants in the etiology of epistaxis: Traditional and novel anticoagulants in epistaxis - Kandemir, Süheyla; Kandemir, Hüseyin (Journal of Surgery and Medicine, 2024)
Background/Aim: There is a dearth of studies addressing the effects of next-generation anticoagulants on epistaxis. The aim of this investigation was to determine whether there are any differences between traditional and next-generation anticoagulants in the etiology of epistaxis. Methods: This retrospective cohort study focused on a total of 7,110 individuals (3,278 females (46.1%) and 3,832 males (53.9%)) diagnosed with epistaxis between 2018 and 2022; the mean age of the patients was 37.7 years. Patient data (age, gender, outpatient and inpatient treatments, relevant laboratory parameters, and treatment evidence) were retrospectively reviewed from a hospital database. The severity of epistaxis was assessed based on treatment notes. Patients with hypertension and those undergoing antiaggregant therapy were excluded from the study. International Classification of Diseases (ICD) codes from the automated system were examined retrospectively. The data were used to establish three patient groups: the first group consisted of individuals taking next-generation oral anticoagulants, the second group consisted of individuals taking traditional oral anticoagulants, and the third group consisted of healthy controls. Results: We found statistically significant differences among the groups in terms of age, the severity of epistaxis, the treatment modality, and laboratory findings (P<0.001); no statistically significant difference was found in terms of gender (P=0.954). Group 2 contained the largest number of hospitalized patients and patients with severe active nosebleeds. Conclusion: Next-generation anticoagulants are more reliable than traditional anticoagulants in terms of the severity of epistaxis, the need for hospitalization, and laboratory results.